279 Endometrial cancer: initial results of conservative hormonal treatment in postmenopausal patients in oncology hospitals of Buenos Aires. (13th November 2020) - Soderini, P; Depietri, V; Crespe, M; Horacio, M; Martin, M; Rosa, G; Aragona, A
Abstract : Objective: To analyze the short and medium-term results of conservative hormonal treatment applied to postmenopausal patients. Material and Method: This is prospective study, started in 1/2015. There were included 4 postmenopausal patients: 2 with endometrioid GH1 adenocarcinoma, and 2 with complex atypical hyperplasia.These patients had BMI> 40, DBT type II, hyperlipidemia, smoking and high cardiovascular risk. All the patients were initially biopsied by hysteroscopy and endocervical disease was ruled out. An abdominal-pelvic MRI was done for evaluating myometrial invasion and defining conservative treatment. All the patients had contraindications for surgery and refused radiotherapy (RT) as treatment. The Hormonal one was by placing SIU-LNG. The Follow-up was done at least 3 – 6 months by pelvis examination, hysteroscopic biopsy and MRI. Results: Median age : 59 years old. In all the cases, the biopsies performed showed a progressive pathological regression to atrophic endometrium in the last controls. There were observed no adverse effects related to the treatment. Currently the patients are alive and free of disease (SG and SLE 100%). Follow up: 24– 72 months. Conclusions: Excellent results were obtained with the use of local hormonal therapy with SIU-LNG in those postmenopausal patients with high surgical risk, and who in turn refuse to receive radiotherapy.